Antibiotic prescription for endodontic infections: a survey of Brazilian Endodontists - Bolfoni, M. R.; Pappen, F. G.; Pereira‐Cenci, T.; Jacinto, R. C. (International endodontic journal, 2018)
Aim To investigate antibiotic prescribing habits reported by Brazilian endodontists in specific clinical situations. Methodology Brazilian endodontists (n = 13 853) were invited to answer an online questionnaire. The questionnaire consisted of two parts: the first part contained personal data such as age, gender, years of experience and location of endodontic practice; the second part included questions regarding their behaviour when prescribing antibiotics in dental practice. The subjects provided their registration number in the Regional Council of Dentistry (RCD) to prevent duplication of data. Data were collected and analysed by SPSS 17.0 (SPSS, Inc., Chicago, IL, USA). Chi‐square and Fisher's exact tests were used to test the significance of possible associations (P < 0.05). Results From the 13 853 questionnaires, a total of 615 were answered (4.44%). The first‐choice antibiotic was amoxicillin (81.5%), followed by amoxicillin + clavulanic acid (30.7%). For acute apical abscesses with intra‐ and extraoral diffuse swelling, fever and trismus, 90.1% reported they would prescribe antibiotics, whilst 88.1% reported they would prescribe antibiotics even without extraoral swelling, fever and trismus, and 20.5% would prescribe antibiotics in cases of chronic apical periodontitis, and sinus tract. The first‐choice antibiotics varied by age of dentist (P < 0.001) and time elapsed since their endodontic graduation (P = 0.001). Conclusions Many endodontists reported prescribing antibiotics in situations where they would not be indicated. Likewise, the general administration of antibiotics was longer in duration than necessary, reinforcing the need of continuous education regarding the use of antibiotics.